Enhancing Early Childhood Learning through Interactive Storytelling: A Study at RA Miftahul Huda - Anita Romawati; Marliana Rindu (EduSpirit : Jurnal Pendidikan Kolaboratif, 2025)
This research aims to explore the effectiveness of interactive storytelling as a method to enhance early childhood learning at RA Miftahul Huda. Early childhood education plays a critical role in laying the foundation for future learning, and interactive storytelling has emerged as a promising approach to engage young learners. This study examines how interactive storytelling, characterized by active participation from both educators and students, contributes to the development of language, creativity, and social-emotional skills among preschool children. The research was conducted at RA Miftahul Huda, a local early childhood education institution, with a focus on children aged 4 to 6 years. Through a combination of observation, interviews, and classroom participation, data were collected to assess the impact of interactive storytelling on children’s learning outcomes. The study also involved analyzing the responses of teachers and parents regarding the integration of this method into the curriculum. The findings of this research indicate that interactive storytelling significantly enhances children’s vocabulary, fosters imaginative thinking, and encourages collaboration among peers. Moreover, the research highlights the positive influence of interactive storytelling on children’s listening skills and their ability to express ideas and emotions effectively. Educators also reported increased engagement and enthusiasm from students during storytelling sessions, demonstrating the method’s potential to foster a love for learning in early childhood. In conclusion, interactive storytelling proves to be an effective and engaging pedagogical approach in early childhood education. It not only supports the cognitive development of young learners but also nurtures their social and emotional growth, making it a valuable addition to the curriculum at RA Miftahul Huda.